Analysis of bird's perching mechanism - Tan, Yu Yii (Nanyang Technological University, 2014)
As the usage of Unmanned Aerial Vehicles (UAVs) in the current industry increases, more research is required to maximize the potential and capabilities. The development of perching UAVs have been crucial as it allows a longer operation time by saving battery when “perched” in the targeted area. By examine closely of the perching mechanism used by birds, the advantages of its complex system may be used for upcoming development perching system of future UAVs. This report presents an experimental study done to analyze the perching behavior of birds that was achieved with the assistance of Flightmasters who had provided trained birds for the experiment. Observations and findings are included in this report, however some data are not collected due to some restrictions.